Main pests affecting to the foreign pistachio varieties growing in Uzbekistan - Kholliyev Asamiddin Turaevich; Khujaev Otabek Temirovich; Nazarova Odina Jumadullaevna (Genius Publishing Group, 2023)
Pistachio is consumed as a valuable fruit around the world. But saving his harvest is not always an easy task. Identifying its pests and developing measures to combat them is one of the main issues facing scientists today
Keywords: pistachio; anapulvinaria pistaciae; geoica utricularia